STUDI PENGELOLAAN DOKUMEN BERITA DI PEMERINTAHAN KOTA BANDUNG DAN KENDALANYA - Abdurrakhman Prasetyadi (Pusbindiklat - LIPI, 2014)
This study is intended to analyze the management of news documents in Bandung City Government in order to know the flow, the role of public relations and any constraints experienced in the process of news document management in Bakominfo Bandung City Government. The method used in this research is a descriptive qualitative method. The data were collected by conducting in-depth interviews to employees and leaders of public relations departments of Bakominfo Bandung City Government. The researcher also conducted participant observation and bibliographical research. The results of this study shows that the news document management is conducted through five digitazion stages. The stages are as follows: news compilation and selection, news document reading using scanner, news document editing, documentation on data basis, and news document presentation to the internal parties. The role of public relations in disseminating information to the public is cooperating with 15 mass media, including the local newspaper to provide information, such as press releases about the activities of organizations/leadership ranks. The constraints experienced by the public relations department of Bandung City Government are the internal factors, such as lack of coordination with other work units, lack of infrastructure and skilled human resources to do reporting and digitizing documents.